Strategies for Utilizing Village Funds for Economic Recovery of Communities Post- Covid-19 Pandemic - Ni Putu Sukrini (Green Publisher Indonesia, 2024)
The end of the Covid-19 pandemic does not immediately change the economic situation of the community. Various efforts have been made by the government, including enhancing economic conditions at the village level. Since 2015, village funds have been directed toward equitable development, and during the pandemic, their use was prioritized for Covid-19 prevention. To support economic recovery, the government established priority policies for utilizing village funds. This study aims to identify the village government’s strategies in using these funds for economic recovery, as well as the obstacles and supporting factors in implementation, and the impacts felt by the community and the village government. The research was conducted in Taro Village, Tegallalang District, Gianyar Regency, using a qualitative descriptive approach through interviews, observations, and documentation. Informants were selected through purposive sampling. The findings indicate that Taro Village Government’s strategies include food security programs, infrastructure development for agriculture, tourism village development, BLT programs, and labor-intensive programs. Challenges faced include limitations in managing village funds according to community needs and inadequate human resources. Supporting factors include community participation, cooperation between village services and customary institutions, and local natural potential. Positive impacts for the community include job creation and business opportunities, while the village government benefits from CSR assistance from companies to support village programs.